Assessment to Enhance and Demonstrate Graduate Attributes - Vedhathiri, Thanikachalam (Journal of Engineering Education Transformations, 2021)
India has to develop engineers with competencies required for independent practice in which the graduates can work similarly to competent senior engineers and managers. Graduate attributes form a set of individually assessable outcomes that are components indicative of the graduate’s capacity to acquire competence to independently practice at the desired level of the industry. In the knowledgebased global economy, the engineering graduates should possess the needed outstanding abilities to solve complex and real-life programs of the fast-growing global industry. A sizable percentage of Indian Engineering graduates are found to be lacking industry-specific skills, competencies and rendered jobless. A snap study on the alumni shows that fine- tuning of assignments based on industrial practice is essential. The SWOT Analysis suggests that the need for continuous quality development programs for engineering students. All the engineering programs are to be accredited under NBA as per the Washington Accord so that the graduate engineers can register in other countries if they migrate. Otherwise, they have to work for a minimum of two years as an intern. India has to establish an Engineering Council for the registration of the engineering graduates as similar to the Architectural Council. The need for industry-focused complex development programs for all students has been identified based on the qualitative research done. It is found that there is an urgent need for graduates to prepare portfolios and plan to acquire desired competence through seminars, research, industry- specific capstone projects, and self-planned practicum. It is suggested to introduce a course on failures, guest lectures on the industrial methods, trends in new technologies, innovations, and offer industry-specific dissertations.